Analysis of clinical research coordinator (CRC) deviation from assigned responsibilities in Sichuan, China based on empirical investigation - Shi, Shuxia; Qin, Shangyuan; Yu, Qin (Frontiers in Medicine, 2026)
ObjectiveExploring the current status and causes of overstepping behavior among clinical research coordinators: providing reference for standardizing CRC responsibilities and safeguarding clinical trial quality and subject safety.MethodsThe research utilized a literature review and semi-structured interviews to design the survey questionnaire, which was disseminated online through WeChat via a Questionnaire Star link. Data were processed for missing values and outliers using IBM SPSS Statistics 29.0 and R software program (version 4.1.2), with categorical variables summarized using frequencies and percentages. The questionnaire was designed independently by our research team (excluding members from participating institutions) and pre-tested on several non-participating clinical trial professionals to verify neutrality. Semi-structured interviews were conducted by two researchers unaffiliated with participating institutions, with cross-checks for consistency.ResultsThe self-designed questionnaire in this study comprised 15 closed-ended questions (eight single-choice and seven multiple-choice items) and two open-ended questions. Both the Scale-level Content Validity Index/Universal Agreement (S-CVI/UA) and the Scale-level Content Validity Index/Average (S-CVI/Ave) exceeded 0.9, while Cronbach’s Alpha coefficient was greater than 0.7, indicating high overall content validity and reliability of the questionnaire. A total of 202 stakeholders in clinical trials participated in the survey, including staff from clinical trial institutions, sponsors/CROs, and SMO personnel. Survey results indicated that 177 respondents (33.71%/87.62%) attributed CRC role overstepping to investigators’ unclear understanding of their own responsibilities and those of CRCs. Meanwhile, 181 participants (38.11%/89.60%) reported that such overstepping frequently occurred when investigators requested CRCs to perform potentially unauthorized tasks. The most common type of overstepping, identified by 152 respondents (31.93%/75.25%), involved CRCs using physicians’ accounts to access hospital management systems for medical record documentation or modification. One hundred seventy-seven participants (29.70%/87.62%) proposed that strengthening investigator management, specifically by prohibiting the sharing of personal login credentials, should be implemented as a key control measure. Chi-square test performed on the collected data revealed no statistically significant differences (p > 0.05) in pairwise comparisons between subgroups.ConclusionCRC role boundary violations frequently correlate with investigators’ insufficient awareness of regulatory requirements and clinical trial protocols. As principal contributors to clinical research, investigators must clearly delineate and fulfill their essential trial-related obligations. Concurrently, CRCs should strictly adhere to Good Clinical Practice (GCP) guidelines and industry standards while assisting investigators, thereby collectively enhancing trial efficiency and quality.